Best Answer

well we can't simiply solve that problem. we must no what y= to solve this. So u can only simpify ok combine like terms. 2y plus 9y is 11y. your answer is 11y+9

Study guides

☆☆

Q: 2y plus 9y plus 9 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(1) 9x-2y=73 (2) 5x-9y=9 from (1) 9x-2y+2y=73+2y => 9x= 73+2y => x = (73+2y)/9 put into (2) 5x-9y = 9 => 5(73+2y)/9 - 9y=9 => 10y/9 + 365/9 -9y = 9 => 10y/9 - 9y = 9 -365/9 = -284/9 => -71y/9 = -284/9 => 71y= 284 => y = 284/71 = 4 and x = (73+2*4) / 9 = 9

It is 12x + 11y + 9.

9x - 2y = 73 . . . . . (a) 5x - 9y = 9 . . . . . (b) (a)*9: 81x - 18y = 657 (b)*2: 10x - 18y = 18 Subtract: 71x = 639 so x = 9 Substitute in (a): 81 - 2y = 73 2y = 8 so y = 4 The ordered pair is (9, 4)

5y = 2y+9 5y-2y = 9 3y = 9 y = 3

9y + 5 = 0 (-5 on both sides)9y = -5 (/9 on both sides)y = -5/9

Related questions

-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5

3x-2y+9+9y-x = 2x+7y+9

(1) 9x-2y=73 (2) 5x-9y=9 from (1) 9x-2y+2y=73+2y => 9x= 73+2y => x = (73+2y)/9 put into (2) 5x-9y = 9 => 5(73+2y)/9 - 9y=9 => 10y/9 + 365/9 -9y = 9 => 10y/9 - 9y = 9 -365/9 = -284/9 => -71y/9 = -284/9 => 71y= 284 => y = 284/71 = 4 and x = (73+2*4) / 9 = 9

2y-5=11y+40 Subtract 2y from both sides -5=9y+40 Subtract 40 from both sides. -45=9y Divide by 9. -5=y

It is 12x + 11y + 9.

9x - 2y = 73 . . . . . (a) 5x - 9y = 9 . . . . . (b) (a)*9: 81x - 18y = 657 (b)*2: 10x - 18y = 18 Subtract: 71x = 639 so x = 9 Substitute in (a): 81 - 2y = 73 2y = 8 so y = 4 The ordered pair is (9, 4)

9 + 9y = 27x -9 -9 9y = 27x - 9 9y/9 = 27x/9 - 9/9 y = 3x -1

Solving for y: 5y = 9 + 2y 5y - 2y = 9 3y = 9 y = 9/3 = 3

5y = 2y+9 5y-2y = 9 3y = 9 y = 3

x = y+3 x+2y = 9 => x = 9-2y y+3 = 9-2y 2y+y = 9-3 3y = 6 y = 2 and x = 5

9y + 5 = 0 (-5 on both sides)9y = -5 (/9 on both sides)y = -5/9

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6